Política urbana e a gestão de feiras livres: um estudo sobre a feira livre do município de Capim Grosso - Bahia - Reis, Gredison de Novais (2023)
This research aims to understand the contributions and limits of territorial planning in urban policy actions in the management and reorganization of the street market in the municipality of Capim Grosso - Bahia. Considered one of the biggest open-air fairs in the Jacuípe Basin Identity Territory, the Capim Grosso fair, traditionally held on Mondays, is characterized by the diversity of products for sale, purchased in other locations and from family farming, and presents aspects of identity and cultural manifestations. The study discusses territorial planning with a view to the applicability of urban policy instruments for better management of the free fair, based on participatory public management, as a process of building public policies. The methodology adopted is based on bibliographical research that involves the study of the art of the subject, documental and also federal and municipal legislation about the urban policy directed to free fairs. With a quali-quantitative approach, the research is configured with a case study of a descriptive, exploratory nature and unsystematic observation, with the application of semi-structured questionnaires/interviews to the stallholders and users/consumers at the Capim Grosso street market, and the municipal government. For the analysis and discussion of the results, the stages of categorization, inference, description and interpretation were followed, which allowed understanding the street market as an economic, social, identity and cultural practice. The research findings pointed out that the fair under analysis directly supports local and regional development, both economically and culturally, however, there is no participatory management in the construction and implementation of public policies aimed at the management, cultural enhancement and maintenance of the fair free in the urban context. Thus, based on the relevant legislation and interviews with traders and users, an urban intervention plan is proposed, with structural measures aimed at better territorial reorganization of the street market.